QUALITATIVE ANALYSIS METHOD OF DETECTION OF WAX CONTENT IN GORENGAN USING SMARTPHONE - Yulia Yulia; Hendri Wasito; Amin Fatoni (Sanata Dharma University, 2018)
Wax is one of the compounds that can be misused to be added to Gorengan, Indonesian fritter, to keep them crispy. Gorengan containing wax is difficult to identify visually, so a quick and easy method of detecting wax content is required. The purpose of this research is to develop and evaluate the analytical performance of detecting wax content in gorengan using smartphone. Gorengan sample was dissolved with hexane and then added reagent that will give discoloration followed by analysis using smartphone. Some analysis performance parameters were evaluated in terms of linearity and detection limit, qualitative analysis capability, precision, and selectivity test. The developed method was also applied in some gorengan samples. The result shows that the detection of wax content in gorengan can be conducted by using reagent consisting of NaOH, Schift, and curcumin (1 : 2 : 2). Performance analysis shows that the linearity measurement at concentration between 10% and 25% has correlation coefficient (r) of 0.9537 with detection limit at concentration of 2% and precision (%RSD) less than 3%. The developed method can be applied for the detection of wax content in gorengan in the market.